An Air‐Stable and Li‐Metal‐Compatible Glass‐Ceramic Electrolyte enabling High‐Performance All‐Solid‐State Li Metal Batteries. Issue 8 (20th January 2021) - Zhao, Feipeng; Alahakoon, Sandamini H.; Adair, Keegan; Zhang, Shumin; Xia, Wei; Li, Weihan; Yu, Chuang; Feng, Renfei; Hu, Yongfeng; Liang, Jianwen; Lin, Xiaoting; Zhao, Yang; et al.
Abstract: The development of all‐solid‐state Li metal batteries (ASSLMBs) has attracted significant attention due to their potential to maximize energy density and improved safety compared to the conventional liquid‐electrolyte‐based Li‐ion batteries. However, it is very challenging to fabricate an ideal solid‐state electrolyte (SSE) that simultaneously possesses high ionic conductivity, excellent air‐stability, and good Li metal compatibility. Herein, a new glass‐ceramic Li3.2 P0.8 Sn0.2 S4 (gc‐Li3.2 P0.8 Sn0.2 S4 ) SSE is synthesized to satisfy the aforementioned requirements, enabling high‐performance ASSLMBs at room temperature (RT). Compared with the conventional Li3 PS4 glass‐ceramics, the present gc‐Li3.2 P0.8 Sn0.2 S4 SSE with 12% amorphous content has an enlarged unit cell and a high Li + ion concentration, which leads to 6.2‐times higher ionic conductivity (1.21 × 10 −3 S cm −1 at RT) after a simple cold sintering process. The (P/Sn)S4 tetrahedron inside the gc‐Li3.2 P0.8 Sn0.2 S4 SSE is verified to show a strong resistance toward reaction with H2 O in 5%‐humidity air, demonstrating excellent air‐stability. Moreover, the gc‐Li3.2 P0.8 Sn0.2 S4 SSE triggers the formation of Li–Sn alloys at the Li/SSE interface, serving as an essential component to stabilize the interface and deliver good electrochemical performance in both symmetric and full cells. The discovery of this gc‐Li3.2 P0.8 Sn0.2 S4 superionic conductor enriches the choice of advanced SSEs and accelerates the commercialization of ASSLMBs. Abstract : A new glass‐ceramic Li3.2 P0.8 Sn0.2 S4 solid‐state electrolyte is developed to simultaneously possess high ionic conductivity (10 −3 S cm −1 level at room temperature), excellent air‐stability (dry room operable), and good Li metal compatibility. It is expected that this finding can help to accelerate the commercialization of all‐solid‐state Li metal batteries.